2012
DOI: 10.1002/mnfr.201100722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant sterols and stanols on intestinal cholesterol metabolism: Suggested mechanisms from past to present

Abstract: Plant sterols and stanols are natural food ingredients found in plants. It was already shown in 1950 that they lower serum low-density lipoprotein cholesterol (LDL-C) concentrations. Meta-analysis has reported that a daily intake of 2.5 g plant sterols/stanols reduced serum LDL-C concentrations up to 10%. Despite many studies, the underlying mechanism remains to be elucidated. Therefore, the proposed mechanisms that have been presented over the past decades will be described and discussed in the context of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
155
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(171 citation statements)
references
References 105 publications
0
155
0
5
Order By: Relevance
“…It corresponds to 2.5 mm. Consequently, dietary cholesterol was excreted in the feces by plant sterol (40). Nevertheless, cholesterol excretion in feces of the AE group did not significantly increase.…”
Section: Discussionmentioning
confidence: 85%
“…It corresponds to 2.5 mm. Consequently, dietary cholesterol was excreted in the feces by plant sterol (40). Nevertheless, cholesterol excretion in feces of the AE group did not significantly increase.…”
Section: Discussionmentioning
confidence: 85%
“…However, more studies are needed to understand whether the phytosterols are able to alter the LXR phosphorylation state. Nonetheless, it is known that systemic LXR activation increases hepatic fatty acid synthesis and steatosis (De Smet et al 2012), and therefore, phytosterols of black bean seed coats can potentially be used to reduce or prevent these abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…3 Role of plant sterols on cholesterol absorption 3.1 Inhibition of cholesterol absorption by plant sterols It is well established that dietary plant sterols have hypocholesterolemic activity in experimental animals and humans 5 . Because being fed a diet of plant sterols increases fecal excretion of cholesterol and its metabolites, it is thought that plant sterols inhibit cholesterol absorption in the intestine.…”
Section: Determinants Of Differential Absorption Of Plant Sterolsmentioning
confidence: 99%
“…Therefore, we concluded that sitosterol does not influence post-micellization processes of cholesterol absorption. Recently, Smet et al summarized the proposed mechanisms responsible for the effects of plant sterols and stanols on intestinal cholesterol metabolism 5 . Although many other interesting mechanisms regulating cholesterol absorption by plant sterols have been suggested, the authors concluded that suppression of micellar solubility of cholesterol by plant sterols is the only equivocally established effect.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation